2012
DOI: 10.1186/1475-2875-11-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of household heads training about the use of treated bed nets on the burden of malaria and anaemia in under-five children: a cluster randomized trial in Ethiopia

Abstract: BackgroundLong-lasting insecticide-treated bed nets (LLITN) have demonstrated a significant effect in reducing malaria-related morbidity and mortality. However, barriers on the utilization of LLITN have hampered the desired outcomes. The aim of this study was to assess the effect of community empowerment on the burden of malaria and anaemia in under-five children in Ethiopia.MethodsA cluster randomized trial was done in 22 (11 intervention and 11 control) villages in south-west Ethiopia. The intervention consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 30 publications
3
40
0
1
Order By: Relevance
“…Most studies reported more than one outcome as shown in S4 and S5 Tables. Of the 25 studies involving intersectoral collaboration which measured pre-post-outcomes compared against disease indicators, such as the number of cases or incidence or prevalence of malaria (15 studies) [ 4 , 30 43 ], dengue (four studies) [ 44 47 ], schistosomiasis (two studies) [ 48 , 49 ], zika (one study) [ 50 ], Japanese encephalitis (one study) [ 51 ], and leishmaniasis (one study) [ 52 ]. Amongst the 16 studies which measured vector variables (adult density, pupae or larval indices) as outcomes eleven studies were dengue [ 44 , 46 , 47 , 53 60 ], followed by two studies on schistosomiasis [ 48 , 49 ], and one on malaria [ 4 ] and on Chagas diseases [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies reported more than one outcome as shown in S4 and S5 Tables. Of the 25 studies involving intersectoral collaboration which measured pre-post-outcomes compared against disease indicators, such as the number of cases or incidence or prevalence of malaria (15 studies) [ 4 , 30 43 ], dengue (four studies) [ 44 47 ], schistosomiasis (two studies) [ 48 , 49 ], zika (one study) [ 50 ], Japanese encephalitis (one study) [ 51 ], and leishmaniasis (one study) [ 52 ]. Amongst the 16 studies which measured vector variables (adult density, pupae or larval indices) as outcomes eleven studies were dengue [ 44 , 46 , 47 , 53 60 ], followed by two studies on schistosomiasis [ 48 , 49 ], and one on malaria [ 4 ] and on Chagas diseases [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…[35][36][37][38] Malaria prevention and effective treatment measures have dramatically expanded in the past decade. Although the UMIS was the first national survey to assess malaria prevalence in Uganda, the prevalence of malaria likely decreased during this interim given the rapid scaleup of malaria control activities.…”
Section: Discussionmentioning
confidence: 99%
“…Because most studies have been carried out in endemic settings, one must be careful transferring these results directly to non-immune travellers with imported non-falciparum malaria. On the other hand, European treatment guidelines are mainly based on data from studies carried out in endemic areas, since there is a paucity of original prospective treatment data for non-immune patients[ 21 ]. It must be acknowledged that in most settings, there are too few participants for large-scale trials assessing ‘one size fits it all’ strategies for non-falciparum malaria in and outside endemic areas.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, there might be a compelling rationale to treat all (including returning travellers) diagnosed with malaria with an ACT irrespective of malaria species[ 21 ]. More or less identical first-line treatments based on ACT for all malaria species would not only simplify treatment schemes and avoid ineffective CQ treatment of unrecognized P. falciparum infection, but also offer logistical benefits in terms of pharmacological management, whilst the need to eliminate P.vivax / P.ovale hypnozoites outside endemic areas has to be accounted for.…”
Section: Introductionmentioning
confidence: 99%